Pengembangan Media Bantu Latihan Bertahan Pada Bola Voli Tahun 2019 - Ramlan Sahputera Sagala; Dicky Edwar Daulay (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2020)
This study aims to develop defense training aids in volleyball 2019. The population in this study was 10 PBV volleyball athletes. Pem.Panjang, 10 PBV athletes. Sukaraja and 10 PBV athletes. 50 in 2019. The results of small group tests involving 20 athletes, 10 PBV Pem.Panjang volleyball athletes and 10 PBV 50 athletes showed that the development of defense stone training tools in volleyball 2019 can be concluded that these defense latiam aids meet the criteria to be continued in trials large groups with conditions after repairs due to the percentage of questionnaire statements between 45% -74%. The results of a large group test involving 30 athletes, 10 PBV Pem.Panjang volleyball athletes, 10 PBV 50 athletes and 10 PBV Sukaraja athletes that the development of defense training aids in the 2019 volleyball game can be concluded that defense training aids meet the criteria for use in helps athlete defense training because the percentage of questionnaire statements is between 78% -85%. So it can be concluded that this defense training aid can be used to train defense.